2013
DOI: 10.2112/jcoastres-d-12-00035.1
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Water Levels to Facilitate Vegetation Change in a Coastal Lagoon Undergoing Partial Tidal Restoration (Cape Cod, Massachusetts)

Abstract: I www.JCRonline.org Smith, S. and Medeiros, K., 2013. Manipulation of water levels to facilitate vegetation cbange in a coastal lagoon undergoing partial tidal restoration (Cape Cod, Massacbusetts) Journal of Coastal Research, 29(6A), 93-99. Coconut Creek (Florida), ISSN 0749-0208.East Harbor is a back-barrier coastal lagoon and salt marsb witbin Cape Cod National Seashore (Massachusetts), wbicb has been undergoing partial tidal restoration since 2002. The current tidal exchange has been sufficient to elevate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Most restoration efforts along the North Atlantic coast of North America and in Australia include restoring tidal flow by placement of culverts or removing/opening tide gates (Bakker and Piersma, 2006;Fell et al, 2000;Haines, 2013;Reiner, 2012;Sinicrope et al, 1990;Smith and Medeiros, 2013;Warren et al, 2002;Winning and Saintilan, 2009). Furthermore, reinstating the tide has been realized using self-regulating tide gates (SRT) in US tidal marshes (Connecticut, (Giannico and Souder, 2005;Roman et al, 1984;Rozsa, 1995Rozsa, , 2012; Rhode Island (DiQuinzio et al, 2002); Massachusetts, (Reiner, 2012); Oregon, Washington state, (Giannico and Souder, 2005), Maine (Adamowicz and O'Brien, 2012) and Australia (Glamore, 2012;Russell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most restoration efforts along the North Atlantic coast of North America and in Australia include restoring tidal flow by placement of culverts or removing/opening tide gates (Bakker and Piersma, 2006;Fell et al, 2000;Haines, 2013;Reiner, 2012;Sinicrope et al, 1990;Smith and Medeiros, 2013;Warren et al, 2002;Winning and Saintilan, 2009). Furthermore, reinstating the tide has been realized using self-regulating tide gates (SRT) in US tidal marshes (Connecticut, (Giannico and Souder, 2005;Roman et al, 1984;Rozsa, 1995Rozsa, , 2012; Rhode Island (DiQuinzio et al, 2002); Massachusetts, (Reiner, 2012); Oregon, Washington state, (Giannico and Souder, 2005), Maine (Adamowicz and O'Brien, 2012) and Australia (Glamore, 2012;Russell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last couple of decades, thinking about the potential impacts of climate change on tidal wetland restoration has evolved from a general awareness to a central focus in the design of ecological engineering projects, especially on the long-term sustainability of restored tidal wetlands (Parker et al, 2012). In this sense, restoration has become much more focused on creating conditions that will develop sustainable and resilient plant communities rather than designing specific historical communities for restoration projects (Critchley et al, 2003;Toogood and Joyce, 2009;Palaima, 2012;Smith & Medeiros, 2013;Hayes et al, 2015). Our results have direct implications for ecological engineering and the maintenance of tidal wetland plant communities' characterised by high biodiversity/resilience to the more frequent inundation effects caused by global warming.…”
Section: Discussionmentioning
confidence: 84%
“…Snedden, Cretini, and Patton (2015) also reported that prolonged inundation of S. patens could result in approximately 90% reduction in belowground biomass, leading to substantial reductions in soil shear strength and erosional resistance. Conversely, Smith and Medeiros (2013) report that discrete stands of S. alterniflora were better able to tolerate constant immersion for 2.5 months without any visible signs of stress. It is assumed that this resilience to inundation is capable over the course of one growing season, but even tolerant plants could not withstand multiple years of persistent inundation (Smith and Medeiros 2013).…”
Section: Spartina Alterniflora and Patensmentioning
confidence: 93%
“…Conversely, Smith and Medeiros (2013) report that discrete stands of S. alterniflora were better able to tolerate constant immersion for 2.5 months without any visible signs of stress. It is assumed that this resilience to inundation is capable over the course of one growing season, but even tolerant plants could not withstand multiple years of persistent inundation (Smith and Medeiros 2013).…”
Section: Spartina Alterniflora and Patensmentioning
confidence: 93%